Strategi Guru Terhadap Bahasa Reseptif Anak Usia Dini - Wahyuni, Iska; Jatmikowati, Tri Endang; Rachman, Angraeny Unedia (Jurnal Pendidikan Anak Usia Dini, 2023)
The research background is that receptive language skills are essential for young children's ability to retell, follow rules, and carry out instructions. This is crucial because it facilitates a child's communication and interaction with their surroundings, supporting the learning process when conducted with teachers. The research objective is to determine the strategies used by teachers to enhance the receptive language skills of young children at SPS Dahlia 64 in Kalisat, Jember Regency. The research is of a qualitative descriptive nature, utilizing data collection techniques such as observation, interviews, and documentation. The research findings regarding the strategies employed by teachers include familiarization activities, storytelling, listening to stories and watching videos, using engaging teaching aids, incorporating movement and songs, promoting collaborative activities, allowing children to choose their own activities so they can discuss what they have done, providing picture books, and engaging in question-and-answer sessions. Teachers also establish closeness with children and reach mutual agreements. They frequently encourage children to talk and involve them in activities, such as asking them to pick up or place objects. In conclusion, teachers employ strategies to stimulate the receptive language skills of young children through a communicative approach, engaging activities with appealing and enjoyable media, making it easier for children to express themselves and communicate their thoughts when interacting with others.